Effects of 60Co-γ rays on in vitro mutagenesis of strawberry - ZHANG Hui-qin; XIE Ming; JIANG Gui-hua; WU Qing; SUN Cong-bo (浙江大学学报. 农业与生命科学版)
Two strawberry cultivars (Toyonoka, Akihime) in vitro were irradiated by 60Co gamma rays from 20 Gy to 100 Gy for induced mutation breeding. The results indicated that all treatments had effects on the growth and development of strawberry, but different cultivars had different sensitivity to the irradiation of gamma rays. And the LD50 was also different, which was 55 Gy for strawberry cultivar‘Toyonoka’ and 64.6 Gy for strawberry cultivar ‘Akihime’. Inhibition was obviously produced by 60Co gamma rays for strawberry cultivar ‘Toyonoka’, which the plants became short in height, blooming time was put back, and the number of flowers was reduced, and this inhibition was more obvious with increase of the irradiation dose. The effect of 60Co gamma rays on flowering was more distinct than that on growth for strawberry cultivar ‘Akihime’. As to the high aberrance and the excellent aberrance, the most suitable dose to strawberry cultivar ‘Akihime’ was 20 Gy, at which the plants had high aberrance percent by 36.53% and much excellent aberrance.